Neighbourhood Environmental Correlates of Perceived Park Proximity in Montreal - Moore, Spencer (Can J Public Health, 2011)
OBJECTIVES: Perceived proximity to recreational settings has been shown to be associated with increased physical activity levels. We examined individual socio-demographic and environmental correlates of perceived park proximity in Montreal to assess targets for ecological interventions to improve physical activity. METHODS: A stratified clustered sampling design was used to collect data on perceived park proximity from 864 adults residing in 300 Montreal census tracts. Perceived park proximity was measured by asking participants if they perceived a park as within walking distance of their home. Objective measures of park proximity and park density were constructed using geographic information systems (GIS). Canada Census data provided information on census tract population density and median income levels. Multilevel logistic regression was used to examine the likelihood of not perceiving a park as proximate. RESULTS: Older adults were more likely to perceive a park as not proximate to their home (OR: 1.04; 95% CI: 1.02–1.07). Perceived park proximity varied across Montreal neighbourhoods with an interclass correlation coefficient of 16.10%. Objective distance to the closest park (OR: 1.45; 95% CI: 1.10–1.92) was associated with adults’ subjective perceptions of park proximity. Residents of neighbourhoods with higher population density (OR: 0.92; 95% CI: 0.87–0.97) and higher average income (OR: 0.45; 95% CI: 0.24–0.87) were less likely to view a park as outside walking distance to their residence. CONCLUSION: Regardless of the actual distance to the park, neighbourhood environmental factors are associated with people’s perceptions of having a park within walking distance of their homes.